Pengaruh Minyak Ikan Dan Minyak Krill Terhadap Kadar Malondialdehid Pada Tikus Putih (Rattus novergicus) Hiperglikemik - Bamahry, Aryanti; Radisu, Indri Meliawati; Karsa, Nevi Sulvita Karsa Sulvita (Rumah Sakit Ibnu Sina, Makassar, 2023)
Hyperglycemia is a condition due to glucose levels in the blood exceeding normal levels. Chronic hyperglycemia will result in increased production of free radicals resulting in oxidative stress. Malondialdehyde (MDA) is a free radical biomarker and oxidative stress in the body. Fish oil and krill oil are anti-inflammatory and antioxidant properties. This study aims to determine the effect of fish oil and krill oil on the levels of Malondialdehyde in Wistar White Rats (Rattus novergicus) hyperglycemic. This study uses a true experimental research type pre and post control. The samples in this study were 24 white wistar rats (Rattus norvegicus) which were divided into 4 groups each consisting of 6 mice, namely the negative control group was given a placebo, the positive control group was given glibenclamide, the fish oil group was given fish oil and the oil group krill was given intervention krill oil for 14 days. The mean malondialdehyde (MDA) levels in each group were negative control group 2.47 μmol / l, positive control group 2.13 μmol / l, fish oil group 1.29 μmol / l and irill oil group 0.77 μmol / l. Based on the results of the One way Anova analysis, a significant value of p less than 0.05 was obtained. Fish oil and krill oil have an effect on reducing levels of malondialdehyde. However, krill oil is more effective in reducing malondialdehyde levels than fish oil.